Sport sociology - Craig, Peter (New Delhi, 2016)
Any study of sport is incomplete without consideration of its social function and structures, its economic impacts both locally and globally, and its political dimension ? particularly when used by nations for competitive gain. Sport Sociology provides a comprehensive overview for any student taking a course on the subject at college or university, including both established and emergent themes, from issues around power, diversity and consumerism through to newer topics such as the digital environment and climate change ? both now covered in new individual chapters. Other chapters have been fully revised to include up-to-date literature and case studies, as well as new key terms and reflective tasks. A new ?Key Thinker? box feature included in each chapter introduces readers to an esteemed theorist relevant for the chapter topic to help link theoretical concepts to practice and offer up suggestive research directions for student assessment.
Keywords: Social Science